2009
DOI: 10.1007/s10584-009-9686-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of climatic trends in data from the agrometeorological station of Bologna-Cadriano, Italy (1952–2007)

Abstract: Agriculture is highly exposed to climate change, as farming activities directly depend on climatic conditions. Knowledge of the extent of such change and of related phenomena will help to answer the questions posed by society about adaptation strategies. The global situation is well described by the Fourth IPCC assessment report (IPCC 2007), but local studies are important to understand the impact and the priorities to adopt in adaptation strategies. In this study a historical set of meteorological data, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…In agreement with our results, most of these studies show that the decline in rainfall is due to a significant decrease in the winter and spring seasons when there was an increase in total dry days, especially in winter (Brunetti et al 2002). Emilia-Romagna in the north of Italy (Pavan et al 2008) showed significant negative trends in these seasons and an analysis of the annual number of rainy days revealed a significant decrease from 1952 to 2007 in Bologna (Matzneller et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, most of these studies show that the decline in rainfall is due to a significant decrease in the winter and spring seasons when there was an increase in total dry days, especially in winter (Brunetti et al 2002). Emilia-Romagna in the north of Italy (Pavan et al 2008) showed significant negative trends in these seasons and an analysis of the annual number of rainy days revealed a significant decrease from 1952 to 2007 in Bologna (Matzneller et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The value of 0.1 mm, typically used as threshold in older studies, is often associated with issues related to instrument resolution and measurement accuracy (Brunetti et al, 2004b). In fact, only about 10% of the analysed articles considers a 0.1 mm threshold while recent studies use a 1 mm threshold in order to minimize the non-homogeneities of WDs detected with low thresholds (Brunetti et al, 2000(Brunetti et al, , 2002(Brunetti et al, , 2004bVentura et al, 2002;Cislaghi et al, 2005;Piccarreta et al, 2006;Fatichi and Caporali, 2009;Bodini and Cossu, 2010;Matzneller et al, 2010;Todeschini, 2012;Romano and Preziosi, 2013).…”
Section: Precipitation Indicesmentioning
confidence: 99%
“…For areas in the central and eastern parts of the continent, spring trends are more important, because of an increase in air temperature and the early‐commencing FFS (Scheifinger et al , ; Auer et al , ; Jylhä et al , ; Goergen et al , ; Potop et al , ; Ustrnul et al , ). Regions under the influence of maritime air masses and the southern part of the continent recorded more pronounced changes in autumn (Matzneller et al , ; Fernández‐Montes and Rodrigo, ; Prior and Perry, ; Harding et al , ). Similar trends were observed by Auer et al () in the higher parts of the Alps, which confirms the oceanic character of mountain climate.…”
Section: Introductionmentioning
confidence: 99%